2017
DOI: 10.1016/j.contraception.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of the community-level provision of Sayana® Press by medical and nursing students in Kinshasa, Democratic Republic of the Congo

Abstract: ObjectivesThe objectives were to assess acceptors' attitudes toward Sayana® Press as a method and toward the mechanism of community-based distribution by medical and nursing (M/N) students, known locally as “DBCs,” in Kinshasa, Democratic Republic of the Congo, and to evaluate the experience of these DBCs.Study designIn 2015, surveys were conducted among (1) acceptors of Sayana® Press on the day of the initial injection, (2) these same acceptors 3 months later and (3) the DBCs providing community-based service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
6
13
0
Order By: Relevance
“…Our findings on the acceptability of DMPA-SC as a method are consistent with the results of the pilot introduction of the method in Burkina Faso, Niger, Senegal and Uganda from 2014 to 2016 [17] , as well as our 2015 pilot in Kinshasa [16] . Our findings on high client satisfaction with self-injection concur with results from studies in Malawi and Uganda [18] , [19] ; clients who self-injected had higher continuation rates than those who received DMPA-SC from providers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings on the acceptability of DMPA-SC as a method are consistent with the results of the pilot introduction of the method in Burkina Faso, Niger, Senegal and Uganda from 2014 to 2016 [17] , as well as our 2015 pilot in Kinshasa [16] . Our findings on high client satisfaction with self-injection concur with results from studies in Malawi and Uganda [18] , [19] ; clients who self-injected had higher continuation rates than those who received DMPA-SC from providers.…”
Section: Discussionsupporting
confidence: 88%
“…A 2015 pilot study in Kinshasa used medical and nursing (M/N) students to deliver DMPA-SC and other methods at the community level. It showed that women were highly satisfied with the method and service received from these providers [15] , [16] . Local Ministry of Health (MOH) officials encouraged further testing of innovative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found that clients in Malawi had similar positive experiences with self-injection as those who participated in studies in Uganda and Senegal; like the women in Malawi, they also felt that self-injecting DMPA-SC was easy and preferable compared to DMPA IM [5,6]. Experiencing fewer side effects has been previously documented as a reason women prefer DMPA-SC compared to DMPA-IM [4,11]. In our study, almost half of clients spontaneously mentioned experiencing no or fewer side effects using DMPA-SC compared to DMPA-IM.…”
Section: Discussionsupporting
confidence: 53%
“…Investments in quality, combined with free care, can therefore improve equity. For short-acting method users, community-level provision may improve their access and use of contraception, although results from such pilots in DRC have thus far been mixed [26,27]. It is, however, important to note that 20-24-year-olds were more likely to receive contraceptive information from health workers or CHWs than 15-19-yearolds.…”
Section: Plos Medicinementioning
confidence: 99%